2006
DOI: 10.1111/j.1748-5967.2006.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of the silk spigots of the green crab spider Oxytate striatipes (Araneae: Thomisidae)

Abstract: The genus Oxytate L. Koch, 1878 comprises a homogeneous group of nocturnal crab spiders that have silk apparatuses even though they do not spin webs to trap prey. We examined the microstructure of the silk spinning apparatus of the green crab spider Oxytate striatipes, using field emission scanning electron microscopy. The silk glands of the spider were classified into three types: ampullate, pyriform and aciniform. The spigots of these three types of silk gland occur in both sexes. Two pairs of major ampullat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(50 reference statements)
2
2
0
Order By: Relevance
“…Previous histological studies reveal the pyriform silks are extruded from small diameter spigots located on the same spinneret adjacent to large diameter spigots that produce major ampullate silks (22). This observation is consistent with the ultrastructure of attachment discs obtained by our SEM studies, which revealed networks of similarly sized small diameter fibers embedded within a cementlike substance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous histological studies reveal the pyriform silks are extruded from small diameter spigots located on the same spinneret adjacent to large diameter spigots that produce major ampullate silks (22). This observation is consistent with the ultrastructure of attachment discs obtained by our SEM studies, which revealed networks of similarly sized small diameter fibers embedded within a cementlike substance.…”
Section: Discussionsupporting
confidence: 90%
“…Based upon observational and histological data, the pyriform gland has been implicated in the production of attachment disc silks, which function to affix dragline silk to substrates (19 -21). SEM data support the spigots of the pyriform gland as being relatively small and numerous, located near the major ampullate spigots on the same spinneret (22). Attachment discs have an important biological function for the spider, as they serve to cement dragline silks to a solid support, anchoring the web to wood, concrete, or other surfaces during web construction for prey capture.…”
mentioning
confidence: 59%
“…The mechanical analysis of this simple anchorage model also lends insight into the unknown mechanical behavior of piriform silk(s). SEM data support the notion that the spigots of the piriform gland are relatively small but numerous, and are located near the major ampullate spigots on the same spinneret 27. We know that piriform spigots are present in most if not all orb‐weaving species,28 and recent studies have identified its protein sequence for the cob‐weaving L. hesperus (black widow spider),10 the orb‐weaving A. trifasciata (banded garden spider), N. clavipes (golden silk spider), as well as for N. cruentata.…”
Section: Theoretical Results and Discussionsupporting
confidence: 75%
“…A gluey material from a combination of a flagelliform and two aggregate glands (Kovoor 1987; Moon & Kim 2005) is produced by most web‐building spiders. The coelotine spider P. spinivulva lacks these triad spigots, as do other wandering spiders, such as the wolf spider Pardosa astrigera (Moon 1998), the funnel‐web spider Agelena limbata (Park & Moon 2002), the green crab spider Oxytate striatipes (Moon & An 2006) and the lynx spider Oxyopes licenti (Moon 2006).…”
Section: Discussionmentioning
confidence: 99%